3D Animation Video Learning Media Contains Character Education to Improve Social Skills - Rahayu, Ni Nyoman Sri; Astawan, I Gede; Ambara , Didith Pramunditya (Universitas Pendidikan Ganesha, 2024)
The problem currently occurring is that there are still many children who need better social skills. Based on this, this research aims to develop 3D animated video learning media containing character education. This research is a type of development research. The model used in developing media is the ADDIE model. The subjects of this research were 2 learning media experts and 2 learning content experts. The test subjects in this research were 3 teachers. The product effectiveness test involved 50 Kindergarten B children. Observation, interviews, and questionnaires are used to collect research data. The instrument used to collect data was a questionnaire sheet. The techniques used in analyzing data are qualitative descriptive analysis, quantitative, and inferential statistics. The research results show that the average assessment result given by learning media experts is 3.75, so it is valid with suitable information. The average assessment result of learning content experts is 3.75, so it is valid. The practicality test results were 95.3% (very practical). The results of the t-test are that there are differences in observation results before and after playing the video. It was concluded that 3D animated video media containing character education can improve social skills for young children. The implication of this research is that the 3D animated video media containing character education used can be used in children's learning activities at school.